The Role of Financial Availability and Entrepreneurship Education in Starting Start-Up Business - Riani, Asri Laksmi; Sawitri, Hunik Sri Runing; Istiqomah, Suryandari; S, Anastasia Riani; QA, Intan Novella; Harsono, Mugi; Endarwati, Indri Sri (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research focuses on new enterprises in Surakarta and its neighboring areas. A quantitative method was used to assess data 104 respondents. This study looks at how the determination to establish a firm, the tranparancy of the sales, dynamic market, internal market, and laws influence on capital investors’ decisions and also the trust of them in the growing of start-up entrepreneurs. PLS-SEM was used to test hypotheses in this interpretive and empiric investigation. Results of this research, the data revealed that tolerance of risk had a beneficial impact on launching a new firm (start-up), supporting the first hypothesis. The hypothesis that financial availability has a positive and also substantial influence toward entrepreneurship education. Finally, supports risk tolerance’s mediation role in the association of the entrepreneurship education and also launching a new firm